Quality assessment of indoor radon measurements. Results of the international radon in-field intercomparison study - S. M. Kiselev; A. M. Marennyy; V. G. Starinskiy; Yu. S. Belskikh; V. V. Shlygin; I. P. Korenkov; N. A. Nefedov; M. A. Marennyy (Радиационная гигиена)
The article presents the results of the international radon in-field intercomparison study for passive radon measurement devices. The tests were organized by the environmental agency of the administrative region of Piemonte (Ivrea, Italy). Coverage of participants was 49 laboratories from 15 countries (Italy, Hungary, France, Great Britain, Lithuania, Russia, Sweden, Spain, Bulgaria, Argentina, Australia, Finland, Ireland, Greece and Slovenia). The certified radon passive devices included SSNTDs and electret detectors. SSNTDs are mostly represented by PADC plastic (CR-39) and nitrocellulose film (LR-115-2) detectors. Radon measuring devices were tested in long-term exposure modes at low and high radon levels (tests 1 and 2) and short-term exposure mode at the simultaneous presence of radon and thoron in the atmosphere (test 3). The intercomparison study was carried out in real conditions of operated buildings with different climatic conditions. The main purpose of this study was to evaluate the quality (accuracy and reliability) of the radon measurements under situations similar to the ones in which devices are normally exposed. In comparison with electrets, solid-state track detectors showed to have generally better reproducibility. For the electrets, the most «comfortable» radon measurement conditions were prolonged exposure at high radon levels. There was no significant fading effect of SSNTD at long-term exposure observed. The paper presents the results of the quality assessment of REI-4 passive device based on LR-115-2 widely used for radon monitoring studies in the Russian Federation.